Implementasi Layanan Bimbingan Klasikal Sebagai Upaya Preventif dan Kuratif Terhadap Kecanduan Game Online pada Siswa SMP Negeri 2 Kuala - Elvidayani Elvidayani; Uli Makmun Hasibuan; Putri Syahrani; Lalu Rifki Sanjaya (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This study uses a qualitative method with a descriptive approach to reveal how the implementation of classical guidance services plays a role as a preventive and curative effort against online game addiction in students of SMP Negeri 2 Kuala. The problem of online game addiction has become a phenomenon that disrupts the learning process and social-emotional development of students. In this study, data were collected through observation, in-depth interviews with BK teachers, homeroom teachers, and several students who were indicated to be addicted, as well as documentation of the guidance program being run. The results of the study showed that classical guidance services were able to provide students with an understanding of the negative impacts of online game addiction and raise awareness to manage playing time healthily. Preventive efforts were made through the delivery of material on time management, the consequences of addictive behavior, and strengthening learning motivation. Meanwhile, the curative approach was applied with further counseling for students who had shown symptoms of severe addiction. BK teachers also involved parents in the student recovery process. In conclusion, classical guidance services have a significant role in overcoming online game addiction if implemented systematically and continuously.